Peranan Metode Pembelajaran Terhadap Minat dan Prestasi Belajar Peserta Didik - Abnisa, Almaydza Pratama; Zubaidi, Zubaidi (STAI Asy-Syukriyyah, 2022)
Learning as a process is designed by educators in creating a variety of innovative students who will be able to increase expertise in knowledge, and in order to build good mastery of learning material. Implementation in learning as the basis for formal learning in which there is communication between the various components of learning. The various components are divided into several categories including the following: the presence of educators, learning materials, and the presence of students. This component will require others such as the existence of media, methods, facilities and infrastructure, the existence of a management of the learning implementation environment, thus forming conditions for implementing existing learning that can achieve the targets of learning. Learning is the key for every individual to produce knowledge. So that knowledge learning can be achieved in a way that is consistent with the stages of individual growth. Learning is closely related to the life goals of students, and the goals will be different from one another. So learning should be carried out with systematic planning. Furthermore, in learning there is a process of guiding students, there is a process of changing directions, namely teaching provided by educators, while learning is carried out by students.